2022
DOI: 10.1590/s2175-97902022e20180
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of ocular hydrogel containing combination of ofloxacin and dexamethasone for the treatment of conjunctivitis

Abstract: Conjunctivitis is an inflammation of the conjunctiva, which covers the white part of the eyeball. It can be caused by allergies, bacterial or viral infection. In situ hydrogels are three-dimensional hydrophilic cross-linked network of polymers. In situ hydrogel provided better therapeutic index when compared to conventional treatment. The present work describes the formulation and evaluation of ofloxacin and dexamethasone based on the concept of pH triggered in situ gelation. Carbopol 934p was used as the gell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was reported that the gels are promising perspectives in wound recovery ( Bhowmik et al, 2012 , Sanjana et al, 2022 ). Hydrogel is a physical barrier and provides moisture, promoting wound healing ( Narayana et al, 2022 ). Furthermore, it also fills irregularly shaped wounds and deals with deep bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the gels are promising perspectives in wound recovery ( Bhowmik et al, 2012 , Sanjana et al, 2022 ). Hydrogel is a physical barrier and provides moisture, promoting wound healing ( Narayana et al, 2022 ). Furthermore, it also fills irregularly shaped wounds and deals with deep bleeding.…”
Section: Introductionmentioning
confidence: 99%